Attitudes of Future Music Teachers Towards Values as a Condition for the Formation of Their Artistic Individuality - Martišauskienė, Elvyda; Tavoras, Vilius (Acta Paedagogica Vilnensia, 2012)
The article discusses the importance of values to future music teachers and value transformations in the contemporary world. Following the methodology by M. Rokeach, it was established that such terminal values as health, happy family, inner harmony, mature love are referred to as most important by future music teachers, whereas wisdom, interesting job, active life are perceived as relevant. Such terminal values as pleasure, salvation, comfortable life, national security, equality, beauty, creation are considered irrelevant. According to the respondents, the most relevant instrumental values are responsibility, intellectuality, honesty, erudition, such values as altruism and sensitivity are important, whereas creation, beauty and imagination are perceived as not important. Such attitudes of future teachers towards values comply with trends in value attitudes expressed by adolescents and youth, which were identified by other researchers, and it is hardly possible to consider them exceptional. The statistical analysis has revealed that future teachers’ attitudes towards these values show a weak correlation with the expression of their artistic individuality, which manifests itself through such parameters as artistry, responsibility, creativity and reflexivity. Similar correlations were identified among the most and least acknowledged values and separate parameters of artistic individuality, except for their positive correlations with imagination, salvation (insight into transcendence), pride, courage, self-control as with particularly relevant values for the growth of artistic individuality. Thus, the purposive deepening of a positive attitude towards these values may serve as a condition for the formation of artistic individuality of future music teachers.